UPAYA PENINGKATAN PRESTASI BELAJAR IPS SISWA KELAS VII-E SMP NEGERI 1 KALITENGAH MELALUI PENDEKATAN COMMUNITY LEARNING - Sukamtini, - (WAHANA PEDAGOGIKA, 2016)
The purpose of this study is to improve learning achievement in social studies class VII-E SMP Negeri 1 Kalitengah the academic year 2015/2016. After applying the method community learning, there are differences in the atmosphere in the classroom. Student learning outcomes showed a good change. Several findings in the can ole researchers based on observations and quantitative data. These things include; 1) The results of the initial conditions IPS Learning Competency describe the diversity of the earth, the process of formation and its impact on community life through learning approach in which the data obtained during the pre-cycle reach the average - average 63.33, and only 50% of students achieving a grade of 75 or> 75. Though ideally should be at least 100% of students got 75 or> 75. 2) the results of study in the first cycle shows there is an increase of learning achievement in from the average class. It arises to 69.89 and as much as 65% students get resolved from the standard. The lowest value was 50 and the highest is 90. 3) The results of study on the second cycle there is an increase learning achievement in the form of the average - average class becomes 83.3 and as much as 90% students get resolved. The lowest value was 70 and the highest is 100.